Games, information, and politics : applying game theoretic models to political science - Gates, Scott (Analytical perspectives on politics., 1997)
Despite the long history shared by game theory and political science, many political scientists remain unaware of the exciting game theoretic techniques that have been developed over the years. As a result they use overly simple games to illustrate complex processes. Games, Information, and Politics is written for political scientists who have an interest in game theory but do not thoroughly understand how it can be used to improve our understanding of politics. To address this problem, Gates and Humes write for scholars who have little or no training in formal theory and demonstrate how game theoretic analysis can be applied to politics. They apply game theoretic models to three subfields of political science: American politics, comparative politics, and international relations. They demonstrate how game theory can be applied to each of these subfields by drawing from three distinct pieces of research.